2018
DOI: 10.1016/j.ejvs.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Telangiectatic Matting is Associated with Hypersensitivity and a Bleeding Tendency

Abstract: TM is associated with both hypersensitivity and a bleeding tendency. This study revealed no significant increase in the incidence of haemostatic abnormalities in patients with TM compared with the control group. Given the significant association with hypersensitivity disorders, the underlying mast cell hyper-reactivity may contribute to both hypersensitivity and a bleeding tendency and predispose patients to TM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 22 publications
0
11
0
2
Order By: Relevance
“…A mast-cell hyperactivity together with a bleeding tendency have been hypothesized as predisposing factors. 204 In 2019, five years' follow-up data showed the satisfying results of a technique injecting foam sclerotherapy (polidocanol) immediately followed by Nd:YAG long-pulse emission. 205 In the same year, a randomized comparative study assessing hypertonic saline, polidocanol and Nd:YAG concluded that sclerotherapy remains the gold standard in vessels >1 mm, while Nd:YAG can have a role in smaller vessels.…”
Section: Significant Recent Data Related To the Meeting Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mast-cell hyperactivity together with a bleeding tendency have been hypothesized as predisposing factors. 204 In 2019, five years' follow-up data showed the satisfying results of a technique injecting foam sclerotherapy (polidocanol) immediately followed by Nd:YAG long-pulse emission. 205 In the same year, a randomized comparative study assessing hypertonic saline, polidocanol and Nd:YAG concluded that sclerotherapy remains the gold standard in vessels >1 mm, while Nd:YAG can have a role in smaller vessels.…”
Section: Significant Recent Data Related To the Meeting Discussionmentioning
confidence: 99%
“…A mast-cell hyperactivity together with a bleeding tendency have been hypothesized as predisposing factors. 204…”
Section: Aesthetic Phlebologymentioning
confidence: 99%
“…O tratamento inicial é baseado em localizar o refluxo proximal não tratado de veias safenas, perfurantes, tributárias ou reticulares 10 . Investigar comorbidades associadas é de grande importância para definição da etiologia da reação, uma vez que se observou maior tendência ao desenvolvimento de matting nos pacientes alérgicos, com distúrbio de sangramento, diagnóstico de asma brônquica ou terapia hormonal em curso 5 .…”
Section: Discussionunclassified
“…Nesse contexto, o matting telangiectásico, também conhecido como nuvem telangiectásica, é um dos mais temidos pelo dano estético e pela dificuldade de tratamento. O matting se refere a vasos com diâmetro inferior a 0,2 mm que podem surgir esporadicamente ou em áreas bem definidas, principalmente nos membros inferiores 5 . A angiogênese e a vasodilatação são fatores associados ao matting, ainda que não se tenha uma causa plenamente estabelecida 6 .…”
Section: Introductionunclassified
“…A probable mast cell-induced pathway and association with hypersensitivity, easy bruising and epistaxis have been described. [22,[25][26][27][28] 6. Nerve injury: Transient saphenous or sural nerve injury usually resolve within four to six months.…”
Section: Telangiectatic Mattingmentioning
confidence: 99%